How digitalization has affected HoReCa industry in Kazakhstan - Bakirov, A.; Baiseitov, S.; Kozhaakhmetova, A.; Orazov, Y. (International School of Economics KAZGUU, Nur-Sultan, 2022)
The following work analyzes the hospitality industry - HoReCa, operating as a segment of the service market. This sector conducts an active marketing policy in the development of digital services, around which marketing relationships with consumers are built. In many ways, today promotion in the HoReCa segment is being built taking into account the ongoing active digital development built on the Internet perception as a main marketing instrument defining the creation of loyalty programs and other important factors in attracting and retaining a client. In HoReCa, digital solutions have their own specifics, an attempt to consider which was made in the framework of this work with the identification of consumer attitudes towards digitalization through a survey.
Keywords: HoReCa industry in Kazakhstan